On Not Taming the Wild Tongue: Challenges and Approaches to Institutional Translation in a University Serving a Historically Minoritized Population - Dávila-Montes, José; González Núñez, Gabriel; Guajardo, Francisco (TTR)

(untitled) (Association canadienne de traductologie, 2019)
A consequence of the development of modern states has been the concept of “minority” as used to refer to subsets of the population that are differentiated from that portion of the population which is seen as the “majority.” These minorities are at times distinguished from each other using terms such as national minorities and immigrant minorities. Some scholars have challenged the distinctions drawn by these constructs. An example of how such constructs are not always accurate can be found in Texas’ Rio Grande Valley, where ethnic and linguistic, immigrant and national, minority and majority are not always clear cut. “The Valley,” as the region is locally known, has a long history of the numerical majority being in a minoritized position. In this context, a local university administered a “speech test” to Mexican American students who enrolled between the 1950s and the 1970s. The purpose, according to Anzaldúa (1987), was to tame their “wild tongue.”  This same university, now transformed, proposes to rehabilitate itself, as it becomes bilingual, bicultural, and biliterate. Accordingly, it now undertakes a systematic effort to bilingualize its operations, starting with the localization into Spanish of its website as conducted by the University of Texas Rio Grande Valley’s Translation and Interpreting Office. A number of terminological strategies and translation challenges stemming from the variegated lectal and diglossic landscapes of the region have arisen, which can be illuminated by the Post-Colonial paradigm found in Translation Studies.